COVID-19 pandemic leading to unidentified, silent-pandemic of vitamin D deficiency in young children: a case report - Dewan, Manasvee; Sharma, Neha; Panda, Pragyan Swagatika; Banerjee, Priyanka (International Journal Of Community Medicine And Public Health, 2021)
Vitamin D is a pro hormone needed for the homeostasis of calcium and phosphorus in the body. This state is crucial for maintaining metabolism, nerve conduction and general cellular functions in the body. Coronavirus disease 2019 (COVID-19) pandemic has led to long-term lockdowns. Schools are closed, people are confined to their homes and outdoor activities are at a halt. This has led to rise in cases of vitamin D deficiency (particularly in infants and toddlers) which is going un-noticed and can further lead us to another pandemic of non-communicable disease - vitamin D deficiency. We have presented a case report of healing rickets in a 19-month-old toddler. We aim to highlight this under-diagnosed and ignored vitamin deficiency that can affect the overall health of our younger generation in this COVID-19 era.